1, 2, 3-Restricted Connectivity of (n, k)-Enhanced Hypercubes. (13th November 2019) - Yu, Hui; Yang, Jiejie; Lin, Limei; Huang, Yanze; Li, Jine; Chen, Riqing
Abstract: The connectivity of a graph is a classic measure for fault tolerance of the network. Restricted connectivity measure is a crucial subject for a multiprocessor system's ability to tolerate fault processors, and improves the connectivity measurement accuracy. Furthermore, if a network possesses a restricted connectivity property, it is more reliable with a lower vertex failure rate compared with other networks. The (n, k) -dimensional enhanced hypercube, denoted by Q_n, k, a variant of hypercube, which is a well-known interconnection network. In this paper, we analyze the fault tolerant properties for (n, k) -enhanced hypercube, and establish the 1 -restricted connectivity of Q_n, k (nk+1) and {2, 3} -restricted connectivity of (n, k) -enhanced hypercube Q_n, k (n=k+1) . Furthermore, we propose the tight upper bound of {2, 3} -restricted connectivity of Q_n, k (n> k+1) . Moreover, we show many figures to better illustrate the process of the proofs.